AUDIENCE RECEPTION ANALYSIS OF THE WORLD CUP RELEVANCE IN LISA’S AND SHAKIRA’S WORLD CUP SONGS - Annisa Nirmala; APRILIA LARASATI; MAULIDA MASYRIFAH; MIRNA MARISSA; MUHAMMAD YUSUF AIMAR (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines and compares how YouTube and TikTok audiences receive Lisa’s and Shakira’s respective World Cup songs, focusing on how each artist’s song is perceived in relation to its relevance to the football/World Cup context. Using Stuart Hall’s Encoding-Decoding theory, this research employs a qualitative descriptive method to analyze public comments collected separately from YouTube and TikTok videos related to each song. The data include audience opinions on the performances, lyrics, football relevance, and overall World Cup atmosphere associated with each song. Findings indicate that Shakira’s song is decoded predominantly through a dominant reading, with audiences treating her presence in a World Cup anthem as expected and legitimate due to her prior association with the world cup in Waka Waka song. Lisa’s song, by contrast, produces a more divided pattern, dominant and oppositional readings cluster among fans defending her performance regardless of football content, while oppositional readings center specifically on the absence of football-related lyrics or imagery. This result suggests that audience decoding of World Cup songs is shaped not only by a song’s own content, but by the audience’s perception of the artist’s authority within football culture, extending Hall’s framework beyond ideological alignment to include artist-specific cultural legitimacy.